Women's interdependence after hysterectomy: a qualitative study based on Roy adaptation model - Fatemeh Goudarzi; Talat Khadivzadeh; Abbas Ebadi; Raheleh Babazadeh (BMC, 2022)
Abstract Background Hysterectomy is a difficult process that some women encounter that can affect their interdependence, but its impact on women's Interdependence has received less attention. Therefore, this study aimed to explain women's Interdependence after hysterectomy. Methods This qualitative study was performed using a directed content analysis approach in Mashhad (Iran). Thirty women with a history of hysterectomy were included in the study by purposive sampling method. Data were collected from August 2018 to November 2019 using semi-structured interviews based on the interdependence mod of the Roy adaptation model until data saturation. Data analysis was performed using MAXQDA software and the deductive approach of Elo and Kingas (J Adv Nurs 62(1):107-115, 2008. https://doi.org/10.1111/j.1365-2648.2007.04569.x ). Results Data analysis led to the production of 537 initial codes from participants' experiences. By merging and categorizing them, the theme of "increasing interdependence" emerged, which consists of 2 categories: "Evolution independence and interaction with important people in life" and "Reinforced support system", that include six subcategories. Conclusion After hysterectomy, women not only feel a strong need for support from family members, especially their husbands, they are also seeking support from health care providers and their colleagues. Before the hysterectomy, it is recommended that family members be consulted to ensure the emotional support and care of women after the hysterectomy. It can help the adaptation to hysterectomy.